Investigation of ramped voltage stress to screen defective magnetic tunnel junctions. (5th December 2017) - Choi, Chulmin; Sukegawa, Hiroaki; Mitani, Seiji; Song, Yunheub
Abstract: A ramped voltage stress (RVS) method to screen defective magnetic tunnel junctions (MTJs) is investigated in order to improve screen accuracy and shorten test time. Approximately 1500 MTJs with 1.25 nm thick tunnel barriers were fabricated for this evaluation, and normal MTJs show a 189% tunnel magnetoresistance ratio, a 365 Ω μ m 2 resistance-area product, and a 1.8 V breakdown voltage, which is enough for applying reliable screen tests. We successfully classified MTJs as normal MTJs having good characteristics or defective MTJs having insufficient endurance and showing resistance degradation after only short-term cycling. Using the RVS screen test with low ramp speed, it is demonstrated that remarkable screening performance and little dependence on temperature are obtained for short test time.